Association between socioeconomic and demographic characteristics and utilization of colonoscopy in the EPIC–Heidelberg cohort. Issue 2 (March 2015) - Hermann, Silke; Friedrich, Susanne; Haug, Ulrike; Rohrmann, Sabine; Becker, Nikolaus; Kaaks, Rudolf
Abstract : We aimed to describe the utilization of colonoscopy and its association with sociodemographic characteristics within the European Prospective Investigation into Cancer and Nutrition (EPIC)–Heidelberg cohort study. We included 15 014 study participants (43% men) of the EPIC–Heidelberg cohort recruited between 1994 and 1998. At baseline recruitment, as well as in the 3-yearly follow-up surveys, study participants completed questionnaires on lifestyle, socioeconomic background variables, health status, and use of medications and medical services, including colonoscopy examinations. The present analyses focused on participants who completed the question on colonoscopy examination in all follow-up rounds. Our results show that by the end of the fourth follow-up round, more than half of all participants of the EPIC–Heidelberg cohort had had a colonoscopy. Colonoscopy was associated with some socioeconomic and demographic characteristics: a positive association with vocational training level as well as overall socioeconomic status level [International Standard Classification of Education (ISCED) classification]. A negative association was found for household size and employment status. Colonoscopy usage increased steeply within the subgroup of participants older than 55 years of age and decreased again within the subgroup of participants older than 75 years of age. Organized colorectal cancer screening should include a written invitation system, to overcome the problem of sociodemographic-related differential awareness of and attendance at colonoscopy examinations. Also, the high proportion of prescreened individuals should be taken into account to avoid unnecessary re-examinations.